7x+4(-x-3)=-39

Simple and best practice solution for 7x+4(-x-3)=-39 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x+4(-x-3)=-39 equation:


Simplifying
7x + 4(-1x + -3) = -39

Reorder the terms:
7x + 4(-3 + -1x) = -39
7x + (-3 * 4 + -1x * 4) = -39
7x + (-12 + -4x) = -39

Reorder the terms:
-12 + 7x + -4x = -39

Combine like terms: 7x + -4x = 3x
-12 + 3x = -39

Solving
-12 + 3x = -39

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 3x = -39 + 12

Combine like terms: -12 + 12 = 0
0 + 3x = -39 + 12
3x = -39 + 12

Combine like terms: -39 + 12 = -27
3x = -27

Divide each side by '3'.
x = -9

Simplifying
x = -9

See similar equations:

| 7x^2+12x+5= | | (x/x-9)-(9/x+9)=18x/x^2-81 | | -33=4x+3x+9 | | 7m-3-2m=-18 | | -2/5(15x-15y) | | 4(2x+4)-6(x+1)= | | 10x^2y^3-6xy^2= | | 4(k-6)=2(2k-8)-2 | | -144=-7x+3(-6x+2) | | 3(d+-8)+4= | | 4(2y-1)=4y+12 | | 3x+4(-4x-4)=-149 | | -8m-7=2+9m-10m | | 3(d-8)+4= | | -14=5-g | | 6a/3b | | 9(7x-7)+4=11x-6 | | 4x-10=x+23 | | -a+8y= | | 3+z/4=-5 | | 2(y+5)=-10 | | c=by+ax | | x=4+53 | | 2.50r+5.30=55.20 | | 1x-4+5x-5=10+16x-10 | | X/3=29/6 | | 6x-3(-6x+15)=-165 | | x-4+5x-5=10+16x-10 | | 4a+8+28=8a | | 5x-6x+x-4+3x= | | 3f-1=19-2f | | 9y-1=6y+5 |

Equations solver categories